PENGARUH PEMBERIAN BERBAGAI TINGKATAN KOMBINASI PERLAKUAN NAUNGAN TERHADAP PERTUMBUHAN ANAKAN KEMIRI (Aleurites moluccana L.Willd) - Desti Nanda Prilia Dewi; Ahmad Basir; Eny Dwi Pujawati (Jurnal Sylva Scienteae, 2020)
This research aims to calculate life percentage on every treatment and analyze the growth of Kemiri (Aleurites   moluccana L. Willd) seedlings to the various interaction between shade or light intensity. The variable of seedling growth includes height, diameter and sum of leaves. This research was conducted in open land area around farms and plantations with flat slope conditions in Padang Anyar roads, Tungkaran, RT 04, RW 02, South Borneo Province for 3 month. The data was analized using factorial Completely Randomized Design (CRD) with 4 treatment. Each replication consists of five sample and every treatment was repeated trhree times so that 60 seeds are needed (4x5x3). The result showed the life percentage of seedlings on every treatment was 100%. Growth under shade shows a significant effect on height of seedling, a very significant effect on diameter of seedling, and not give significant effect for sum leaves, known that 50% shade the best give effect to average response toward the increase of tall was 43,73 cm, stem diameter was 0,73 cm and sum of leaves was 13,8 leaves). Keywords: Growth; Kemiri; Shade